Orthodontics and Genetics - Vieira,Alexandre R. (2019)
Abstract Introduction: Genetics has been suggested as an explanation for the etiology of malocclusions, although some questions, due to the perception that genetic inheritance is tied to a monogenic or Mendelian form of inheritance. Objective: This paper describes the inheritance of malocclusions, highlighting the areas of knowledge where research has explored mechanisms that explain deviations in patterns of craniofacial growth. Conclusion: Malocclusions have a complex or multifactorial pattern of inheritance, where more than one gene is involved in the development of the phenotype. There is also the possibility that the environment influences malocclusions.